Analysis of nature-based treatment of surface water runoff from an informal settlement to irrigate vegetables - Lubobo, Lwandile (Department of Environmental and Geographical Science, 2025)
An increasingly common feature among cities in the Global South (including South Africa) is informal urban settlements (IS). This study was conducted to analyse and make a comparative analysis of the physicochemistry of the soil, and nutrient concentration in crops following irrigation with biofiltration-treated surface runoff from IS. Municipal Treated Water (MTW) was used alongside Biofiltration-treated Water (BTW) to irrigate crops for nine months. Three soil treatments were prepared along each irrigation system mirroring each other: 1) control soil, 2) duckweed-treated soil, and 3) biochar-treated soil. Bulbous (belowground) and leafy (aboveground) crops were selected for the experiment. Following each successive harvest during the experimental period, soil samples from a depth of 10 cm were collected and analysed for Soil Organic Carbon (SOC), Sodium (Na+), Cations herein referred to as Exchange Capacity (CEC), Zinc (Zn+), and Iron (Fe+). In addition, the concentration of macro-and micronutrients (N, P, Ca, Mg, Na, Mn, Fe, and Zn) levels of the resulting produce were collected of each successive harvest and analysed at the end of the experiment. Compared with the concentration found in MTW-irrigated soil, the results from the experiment revealed that the concentration of Na +, Ca2 +, Zn+, and CEC was relatively high. Moreover, the results revealed that the concentrations of Zn and Na as measured by range in lettuce, spinach, and beetroot were high. These values were within the World Health Organization [WHO] guidelines and laboratory norms for the concentration of nutrients in vegetables for human consumption. However, the concentration of Na in spinach irrigated using BTW was higher than the laboratory norms and the WHO guidelines. Long-term monitoring and evaluation of soil physicochemistry and soil nutrient changes from BTW irrigation are required.